Assessment and manifestation of central sensitisation across different chronic pain conditions. (5th November 2017) - Arendt‐Nielsen, L.; Morlion, B.; Perrot, S.; Dahan, A.; Dickenson, A.; Kress, H.G.; Wells, C.; Bouhassira, D.; Drewes, A. Mohr
Abstract: Different neuroplastic processes can occur along the nociceptive pathways and may be important in the transition from acute to chronic pain and for diagnosis and development of optimal management strategies. The neuroplastic processes may result in gain (sensitisation) or loss (desensitisation) of function in relation to the incoming nociceptive signals. Such processes play important roles in chronic pain, and although the clinical manifestations differ across condition processes, they share some common mechanistic features. The fundamental understanding and quantitative assessment of particularly some of the central sensitisation mechanisms can be translated from preclinical studies into the clinic. The clinical perspectives are implementation of such novel information into diagnostics, mechanistic phenotyping, prevention, personalised treatment, and drug development. The aims of this paper are to introduce and discuss (1) some common fundamental central pain mechanisms, (2) how they may translate into the clinical signs and symptoms across different chronic pain conditions, (3) how to evaluate gain and loss of function using quantitative pain assessment tools, and (4) the implications for optimising prevention and management of pain. The chronic pain conditions selected for the paper are neuropathic pain in general, musculoskeletal pain (chronic low back pain and osteoarthritic pain in particular), and visceral pain (irritable bowel syndrome in particular). The translational mechanisms addressed are local and widespread sensitisation, central summation, and descending pain modulation. Significance: Central sensitisation is an important manifestation involved in many different chronic pain conditions. Central sensitisation can be different to assess and evaluate as the manifestations vary from pain condition to pain condition. Understanding central sensitisation may promote better profiling and diagnosis of pain patients and development of new regimes for mechanism based therapy. Some of the mechanisms underlying central sensitisation can be translated from animals to humans providing new options in development of therapies and profiling drugs under development.